Visual communication for landscape architecture - Entwistle, Trudi, 4 0 16; Knighton, Edwin; 5 (London : AVA Publishing, 2013)
Demonstrates how and where a range of visual communication skills are needed to inform a design process, why they are essential, and illustrates how representational techniques can be sensitively applied in different contexts appropriate to a diverse range of design challenges and encourages experimentation with contemporary techniques.
Includes bibliographical references and index.
Adult;Adult.
Keywords: 2 -- 0; 6; Technique.;Practice. -- Landscape architecture.;Landscape architecture;Landscape architecture -- 20; 20; 2